PEMANFAATAN LIMBAH AMPAS TEBU DENGAN MENGGUNAKAN HCl SEBAGAI AKTIVATOR UNTUK MENGURANGI DAMPAK LINGKUNGAN DARI LIMBAH INDUSTRI TAHU - Hatina, Surya (Politeknik Negeri Sriwijaya, 2015)
The research aims to determine the effectiveness of active carbon from sugarcane bagasse with activator substance of HCl in decrease the value of COD and TSS and than in increase the value of DO and pH in tofu liquid waste.The optimum condition of decrease the value of COD and TSS and also increase the value of DO and PH in tofu liquid waste is circulation time at 12 hours of fixed bed reaktor. The results of the research show that decrease the value of COD from 123,7 mg/L to 41,6 mg/L or 66,37 %, decrease the value of TSS from 335 mg/L to 103,8 mg/L or 69,1 %, increase the value of DO from 1,86 mg/L to 7,6 mg/L or 75,52 % and increase the value of pH from 3,53 to 4,66.